Exegesis, theology, and childhood: a preliminary state of the art in Latin America. - Vega, Alejandra (2021)
The following article develops a state of the art of the exegetical reflections carried out on the theme of childhood published in the journals Vida y Pensamiento and Ribla in the Latin American context. The reflections that are considered to be the central ideas of the proposals will be subtracted from the readings; to finally outline some attributes that have been associated with childhood according to the interpretations of certain biblical texts on the basis of: determining moral principles, idealization, mythologization and centralization of childhood and classification of the person in binary categories.